Energy optimization and scheduling of natural gas cogeneration industrial park considering photovoltaics - Tang, Yizhong; Chuanxiu; Cheng, Yueliang; Cang, Wei (Transactions on Environment, Energy and Earth Sciences, 2024)
Combined heat and power (CHP) has important application value for realizing sustainable energy development and building a green and low-carbon society, but the complex internal energy structure and equipment coupling relationship also brings challenges to its operation optimization. In this paper, the energy optimization scheduling is studied on the natural gas cogeneration industrial park microgrid, and a multi period dynamic optimization scheduling model for the natural gas cogeneration industrial park microgrid with the goal of minimizing operating costs is established. The network operation characteristics constraints of the cooling network, heating network, power supply network, and gas supply network is considered, as well as the impact of various types of energy storage devices on microgrid scheduling. Based on the scenario method, a industrial park microgrid energy optimization scheduling model considering random fluctuations in photovoltaic output is established. Measures such as quickly adjusting the energy storage and discharge power of the energy storage device are taken to balance the uncertain fluctuations in photovoltaic output. Taking a natural gas cogeneration industrial park microgrid as an example, the correctness and effectiveness of the proposed optimization scheduling model are verified. The calculation results show that the obtained microgrid operation scheduling scheme can effectively save energy consumption and reduce microgrid operation costs; The collaborative operation of multiple types of energy storage devices can more effectively reduce the operating costs of microgrids and is conducive to smoothing out the uncertain fluctuations of photovoltaic power generation.